1964
DOI: 10.1002/aic.690100514
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal dispersion of thermal energy through porous media with a flowing fluid

Abstract: X x = Martinelli momentum transfer parameter [ ( d P / = mole fraction solute in liquid, dimensionless = mole fraction solute in gas, dimensionless d2) L / ( d p / d ) G] l ' ' , dimensionless y y* = composition of vapor in equilibrium with annular liquid; defined by Equation ( 6 ) , dimensionless p p Subscripts u = annular liquid film e = entrained liquid G = gas phase L = liquid phase LITERATURE CITED = fluid viscosity, lb. mass/(ft.) (hr.) = fluid density, lb. mass/cu.ft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

1966
1966
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 24 publications
(8 reference statements)
4
17
1
Order By: Relevance
“…Interestingly, the results presented here show a more rapid increase in thermal dispersion with velocity (Figure 10) compared to Green et al 's [1964] results, possibly due to the larger thermal conductivity of the matrix as mentioned earlier. In a theoretical context, Yuan et al [1991] established a square relationship and concluded that the coefficient (in this case βl,t) is a function of porosity as well as fluid and solid thermal parameters.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Interestingly, the results presented here show a more rapid increase in thermal dispersion with velocity (Figure 10) compared to Green et al 's [1964] results, possibly due to the larger thermal conductivity of the matrix as mentioned earlier. In a theoretical context, Yuan et al [1991] established a square relationship and concluded that the coefficient (in this case βl,t) is a function of porosity as well as fluid and solid thermal parameters.…”
Section: Discussionsupporting
confidence: 65%
“… Green et al [1964] conducted laboratory experiments in ideal porous media (glass spheres) with advective flow to derive the effective thermal conductivity. They suggested the following empirical relationship for the thermal dispersion coefficient DltD0t=n·(vsd50D0t)m. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat transported by temperature gradients within the is also transported by the moving water itself and differential convection occurs due to the different flow pathways that are possible in porous media. These variations in magnitude and direction of the velocity field at the pore-scale create the so-called thermal dispersion (l d ) [15,16]. In addition, differential heat transport due to the heterogeneity of the permeability field at macroscopic scales also contributes to thermal dispersion [12,15,17e19].…”
Section: Thermal Dispersionmentioning
confidence: 99%
“…Then heat is transported by the moving water, and differential advection occurs due to the different flow pathways that are possible in porous media. This process is called thermal dispersion, and is generated by microscale mixing of the pore-scale interstitial water [15,16] as well as by differential transport in macroscale geological heterogeneities [12,17e19]. Usually, the dominant process is thermal diffusion [15].…”
Section: Introductionmentioning
confidence: 99%